Pengembangan “pHelper” Kalkulator pH Larutan Berbasis Web Sebagai Media Pembelajaran Kimia - Winoto, Sebastian Wilbert; Galih, Aileen Vitta Budiman; Awahita, Himeriko; Irmita, Luthfia Ulva (Orbital: Jurnal Pendidikan Kimia, 2023)
In the 21st century and approaching the upcoming Industrial Revolution 5.0, advancements in science education are of paramount importance. Moreover, chemistry and science education in the upcoming Industrial Revolution 5.0 will heavily rely on technology. This research introduces "pHelper," a web-based pH solution calculator designed as an interactive chemistry learning media to address the challenges of advancing chemistry education through technology integration. The research aims to assess the effectiveness of pHelper through validation tests and analyze student responses to this innovative tool. The research methode use is R&D (Research & Development) with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is in the form of assessment sheet validation test and student responses. The results of the validation test for the pHelper learning media met the valid criteria with a validity of 85.3% and the students' responses to the pHelper learning media met the very good criteria with a value of 87%. By merging technology and chemistry education, this research contributes to the evolution of science learning methodologies in preparation for the imminent Industrial Revolution 5.0 challenges.